Biohydrogen production by Clostridium butyricum EB6 from palm oil mill effluent - Chong, Mei Ling; Abdul Rahim, Raha; Shirai, Yoshihito; Hassan, Mohd Ali (Elsevier, 2009)
A hydrogen producer was successfully isolated from anaerobic digested palm oil mill effluent (POME) sludge. The strain, designated as Clostridium butyricum EB6, efficiently produced hydrogen concurrently with cell growth. A controlled study was done on a synthetic medium at an initial pH value of 6.0 with 10 g/L glucose with the maximum hydrogen production at 948 mL H2/L-medium and the volumetric hydrogen production rate at 172 mL H2/L-medium/h. The supplementation of yeast extract was shown to have a significant effect with a maximum hydrogen production of 992 mL H2/L-medium at 4 g/L of yeast extract added. The effect of pH on hydrogen production from POME was investigated. Experimental results showed that the optimum hydrogen production ability occurred at pH 5.5. The maximum hydrogen production and maximum volumetric hydrogen production rate were at 3195 mL H2/L-medium and 1034 mL H2/L-medium/h, respectively. The hydrogen content in the biogas produced was in the range of 60–70%.